Lock and key a novel - Dessen, Sarah (New York, N.Y Viking, 2008)
When she is abandoned by her alcoholic mother, high school senior Ruby winds up living with Cora, the sister she has not seen for ten years, and learns about Cora's new life, what makes a family, how to allow people to help her when she needs it, and that she too has something to offer others
A Junior Library Guild selection
1
Keywords: Abandoned children -- Juvenile fiction; Child abuse -- Juvenile fiction; Families -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Abandoned children -- Fiction; Child abuse -- Fiction; Emotional problems -- Fiction; Families -- Fiction; Interpersonal relations -- Fiction; Self-actualization (Psychology) -- Fiction; Young adult fiction